O najstarijem poznatom spomenu grada Tešnja 1461. godine / About the Oldest Known Mention of Tešanj in 1461 - Filipović, Emir O. (Journal of the Faculty of Philosophy in Sarajevo (History, History of Art, Archeology) / Radovi (Historija, Historija umjetnosti, Arheologija), ISSN 2303-6974 on-line, 2018)
About the oldest known mention of the town of Tešnja in 1461.